Ideal pharmacokinetic profile of dotinurad as a selective urate reabsorption inhibitor. Issue 3 (June 2020) - Omura, Koichi; Miyata, Kengo; Kobashi, Seiichi; Ito, Azusa; Fushimi, Masahiko; Uda, Junichiro; Sasaki, Tomomitsu; Iwanaga, Takashi; Ohashi, Tetsuo
Abstract: Dotinurad, a novel selective urate reabsorption inhibitor (SURI), has potent inhibitory effects at low doses on the uptake of urate by urate transporter 1 (URAT1, solute carrier family 22 member 12 [SLC22A12]), localized at the apical membrane of renal proximal tubular cells. This study sought to clarify the pharmacokinetic (PK) profile of dotinurad. In rats, monkeys, and humans, the apparent distribution volume (0.257, 0.205, and 0.182 L/kg, respectively) and oral clearance (0.054, 0.037, and 0.013 L·h −1 ·kg −1, respectively) of dotinurad were very low, whereas plasma and luminal concentrations were adequately maintained at high levels. In addition, species differences were scarcely observed with plasma protein binding of 99.4%. The main metabolite was dotinurad glucuronide (no specific metabolites in humans), and percentage excretion of unchanged dotinurad was low in all the investigated species. The risk of drug interaction with dotinurad was expected to be low, because it weakly inhibits metabolic enzymes such as cytochrome P450 (CYP). In conclusion, low-dose dotinurad exhibited excellent pharmacological effects as well as ideal PK properties as a SURI. Graphical abstract: Image 1